A stable free tetragermacyclobutadiene incorporating fused-ring bulky EMind groups. Issue 18 (22nd January 2018) - Suzuki, Katsunori; Numata, Yasuyuki; Fujita, Naoko; Hayakawa, Naoki; Tanikawa, Tomoharu; Hashizume, Daisuke; Tamao, Kohei; Fueno, Hiroyuki; Tanaka, Kazuyoshi; Matsuo, Tsukasa
Abstract : The first coordination-free cyclobutadiene (CBD) germanium analogue, tetragermacyclobutadiene, has been obtained as room-temperature stable dark red crystals. Abstract : The first free cyclobutadiene (CBD) germanium analogue was obtained as room-temperature stable dark red crystals via the reaction of the bulky EMind-substituted 1, 2-dichlorodigermene with lithium naphthalenide. The cyclic 4π-electron antiaromaticity is essentially stabilized by the polar Jahn–Teller distortion in the germanium CBD producing a planar rhombic-shaped charge-separated structure.